Early Ischemic Blood Brain Barrier Damage: A Potential Indicator for Hemorrhagic Transformation Following Tissue Plasminogen Activator (tPA) Thrombolysis? - Jin, Xinchun; Liu, Jie; Liu, Wenlan (Current Neurovascular Research, 2014)
Tissue plasminogen activator (tPA) thrombolysis, remains to be the only United States Food and Drug Administration (FDA) approved treatment for acute ischemia stroke. However, the use of tPA has been profoundly constrained due to its narrow therapeutic time window and the increased risk of potentially deadly hemorrhagic complications. TPA-associated hemorrhagic transformation (HT) often occurs as a result of catastrophic failure of the blood brain barrier (BBB), wherein the affected cerebral capillaries can no longer hold blood constituents. Due to its direct contribution to edema and HT, reperfusion-associated BBB damage has been extensively studied, while BBB damage that occurs within the thrombolytic time window is largely neglected. Of note, ischemia-induced BBB damage in the early stroke stages is increasingly appreciated to negatively affect the safety and efficacy profiles of thrombolytic therapy for ischemic stroke. In this review, we discussed the recent findings of spatio-temporal evolution of BBB injury in the early stages of cerebral ischemia and its association with intracerebral hemorrhage following tPA thrombolysis. The increased understanding of early ischemic BBB damage and its close link to tPA-associated HT is of particular importance for developing new preventive and therapeutic strategies to reduce the hemorrhagic complications in stroke thrombolysis.
Keywords: hemorrhage transformation